THE QUESTION OF MODERN SYSTEMATIZATION OF DENTAL CARIES IN UKRAINIAN CHILDREN - L. Khomenko; N. Bidenko (Ukrainian Medical Stomatological Academy, 2016)
To represent the scientific achievements of Ukrainian dental researches we have to use modern terms and classifications accepted by most countries concerning to main stomatological diseases. It is particularly important in paediatric dentistry due to many peculiarities of children's dental caries and high possibility of its prevention on early stages of tooth developing. Objective. The aims of research are to analyze and systematize the most used dental caries classifications in paediatric dentistry and rationalization the application of International Caries Detection and Assessment System (ICDAS) in Ukrainian children. Methods. Analysis of information about the most used dental caries classifications in spite of historical aspect and about ICDAS backgrounds, main principles and opportunities. Results. The first idea of caries classification belonged to G.V.Black. He related the clinical practice of dentistry to a scientific basis. Such classification is still popular but activity of caries process and its initial stages aren't included in it. DMFt, DMFs are recommended by WHO for epidemiological dental investigations, these index not only reflects level of caries intensity, but also do not displays the initial stages of caries development and its activity. The classification, used in Ukraine, comprised by Lucomskyi (1949) describes acute and chronic caries, initial, superficial, middle and deep caries. However differential diagnostics between middle and deep caries is difficult to be performed, especially in children, due to various thickness of dentine in different tooth areas. Furthermore the results of researches show mismatch between deepness of cavity and pathonmorphological changes in the pulp-dentinal complex. It is the cause why the using of terms "caries of enamel", "caries of dentine" and "caries of cementum" are more preferable. The terms "acute caries" and "chronic caries" are not quite accurate and according to pathomorphology, and have to be replaced with terms "active, advanced carious lesions" and inactive or arrested caries. International Caries Detection and Assessment System (ICDAS) based on visual and tactile exploring of caries cavity was proposed by the scientific group in 2002. It is a simple, logical, evidence-based system for detection and classification of caries in dental education, clinical practice, dental research, and dental public health The ICDAS concept is the use of a standardized system, based on best available evidence for detecting early and later stages of caries severity, should lead to the acquisition of higher quality of information which could then be used to inform patient about appropriate diagnosis, prognosis, and clinical management of dental caries at both the individual and public health levels. The International Caries Classification and Management System - ICCM - deliberately involves a range of options designed to accommodate the needs of different users through the ICDAS (International Caries Detection and Assessment System) domains of clinical practice, dental education, research and public health. The ICCM system seeks for providing a standardized method on overall caries classification and management, otherwise recognizes fully that there are different ways for implementing such systems locally. ICCMS™ found on the evidence-based ICDAS system for the staging of caries. The ICCMS™ is a health outcomes focused system that aims to maintain health and save tooth structure. Staging of the caries process and activity assessment is followed by risk-adjusted preventive care, control of initial non-cavitated lesions, and conservative restorative treatment of deep dentinal and cavitated caries lesions. These systems are also available for paediatric dentistry. Conclusions. • Deems, it is expedient to use the terms "active, advanced carious lesions" instead of"acute caries" and inactive or arrested caries instead of "chronic caries". It should be limited use of terms "medium caries" and "deep caries" and distinguish "caries of enamel", "caries of dentine" and "caries of cementum". • ICDAS II and ICCMS are acceptable for scientific researches and practical paediatric dentists of Ukraine.